Correlation between body mass index (BMI) and blood glucose level among people in RMCI Jakarta: A cross-sectional study - Yuliawuri, Hartiyowidi; Handoko, Savian Moses; Simarmata, Aplina Krismutia; Wibowo, Jeffrey (Science Midwifery, 2024)
Obesity is a condition where an individual's body weight is abnormal (BMI >30), leading to excessive fat accumulation. This condition can induce type 2 diabetes mellitus, which results in abnormal insulin production, causing blood sugar levels to spike. This study aims to determine the strength of the correlation between BMI and blood glucose level using a cross-sectional method. We used bivariate data collection, and Pearson's method to determine the strength of the correlation between these two variables. In this study, data from 102 individuals were collected from people in Reformed Millenium Center Indonesia (RMCI) Jakarta. The correlation between BMI and blood glucose levels with r value 0.82 and significance 2-tailed p-value 0.411. The analysis showed a weak positive relationship, but the correlation is not statistically significant. A suggestion for future research is to use body fat percentage as a reference instead of BMI.